Coagulation F13A1 V34L, fibrinogen and homocysteine versus conventional risk factors in the pathogenesis of MI in young persons. Issue 4 (4th July 2018) - Vishwajeet, Vikarn; Jamwal, Manu; Sharma, Prashant; Das, Reena; Ahluwalia, Jasmina; Dogra, Rupinder Kaur; Rohit, Manoj Kumar
Abstract: Background: The pathogenesis of myocardial infarction (MI) involves environmental and genetic risk factors, with the latter putatively playing significant roles in younger patients. Genetic variability in coagulation factors comprises one such group. The coagulation factor 13 subunit A ( F13A1 ) Val34Leu polymorphism (rs5985) has yielded variable findings in literature, with no prior South Asian data. Methods: We studied the frequency of this polymorphism using the amplification-created restriction-enzyme site (ACRES) polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) in 101 MI patients aged below 40 years and 103 controls along with plasma fibrinogen and serum homocysteine levels. Results: The distribution of Val/Val, Val/Leu and Leu/Leu genotypes was similar among cases (72.3%, 26.7% and 1.0%) and controls (78.6%, 19.4% and 1.9%, respectively). Val and Leu allele frequencies were 85.6% and 14.4% among patients and 88.3% and 11.7% among controls, respectively ( p  = .416). Mean plasma fibrinogen was higher in patients vis-à-vis controls (3.1 versus 3.7 g/l; p  < .001) but homocysteine was elevated in both patients (52%) and controls (67%) ( p  = .225). Multivariate analysis revealed hypertension ( p  < .001, OR 6.16) and smoking ( p  < .001, OR 5.48) to impart strongest risk followed by positive family history, plasma fibrinogen levels and male gender. Conclusions: Despite its small sample size, this first South Asian study suggests neither protective nor deleterious effects of the F13A1 Val34Leu polymorphism on the risk of MI in young persons. The Leu allele frequency is intermediate to that reported from the West and the Far East. Traditional risk factors contribute greatly to risk even in younger MI patients in South Asia.